Catalogue of Turkish Manuscripts in the Library of Leiden University and Other Collections in the Netherlands. Minor Collections. - Schmidt, Jan (9ef1efea-7113-4033-be55-1800da653ae5, 2012)
From as early as the 1600s, Dutch scholars and scholarship have displayed a keen interest in the studies of the Islamic world. Over the centuries, they have collected a wealth of source texts in various languages, Turkish texts being prominent among them. The present catalogue is the fourth and final volume in a series that covers the Turkish manuscripts preserved in public libraries and museums in the Netherlands. The volume gives a detailed description of Turkish manuscripts in minor Dutch collections, found in libraries and museums in Amsterdam, Groningen, The Hague, Leiden, Rotterdam and Utrecht, which hitherto have received little or no attention.